2014
DOI: 10.5209/rev_hics.2014.v19.45606
|View full text |Cite
|
Sign up to set email alerts
|

Facebook como herramienta educativa en el contexto universitario

Abstract: Resumen:Esta investigación estudia el uso de Facebook por parte de los estudiantes de primero de grado de Publicidad y RR.PP (Universidad de Alicante) para el aprendizaje de la asignatura Comunicación y Medios Escritos. La metodología empleada es la encuesta, realizada a 76 alumnos durante el mes de Enero de 2013. Los resultados muestran una mejora del proceso de enseñanza-aprendizaje. La red social sirve para compartir materiales, prácticas y resolver dudas, incentivando el aprendizaje colaborativo. Los alumn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The use of social networks as an educational tool can improve motivation, collaboration and communication, breaking down time and space barriers [9]. These tools allow students to provide mutual support in a specific and original way, which is very difficult in the student-teacher relationship.…”
Section: Social Network Education and Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of social networks as an educational tool can improve motivation, collaboration and communication, breaking down time and space barriers [9]. These tools allow students to provide mutual support in a specific and original way, which is very difficult in the student-teacher relationship.…”
Section: Social Network Education and Entrepreneurshipmentioning
confidence: 99%
“…In the educational field, they can be used to enhance communication between groups of people, make them feel part of a community and cooperate with each other in common tasks. In addition, they are excellent tools for breaking the space-time barriers as well as the boundaries of current educational systems [9]. This fact offers an opportunity to integrate social networks as a way of training at the university level [10].…”
Section: Introductionmentioning
confidence: 99%
“…Según Padilla (2012), las redes sociales ofrecen herramientas potenciales para promover la innovación educativa y queda demostrado que pueden ayudar a acercarse mejor al alumnado. Los beneficios comparecen vinculados a la alfabetización digital, a la expansión creativa, al aprendizaje colaborativo, a la motivación y al aprendizaje autónomo, al desarrollo crítico, así como al acercamiento a la inmediata realidad profesional (Ruipérez y García, 2012;Bueno y Hanninen, 2012;García Manso, 2012;Iglesias y González, 2014). Pero ello exige disposición, recursos y competencias tanto al profesorado, como a los centros e instituciones educativas, lo que ha convertido ambos aspectos en objeto de estudio (Imbernón, Silva y Guzmán, 2011;Marcelo, Yot y Mayor, 2015).…”
Section: Principales Conclusiones De Los Artículos Analizadosunclassified
“…According to Padilla (2012), social networks offer potential tools to promote educative innovation and it is demonstrated that they might help in better approaching students. The benefits appear linked to the digital alphabetization, creative expansion, collaborative learning, motivation and the autonomous learning, critical development, as well as the approach to the immediate professional reality (Ruipérez and García, 2012;Bueno and Hanninen, 2012;García Manso, 2012;Iglesias and González, 2014). But this demands disposition, resources and competences both to the teachers, as well as to the teaching centers and institutions, which has turned both aspects in subject of study (Imbernón, Silva and Guzmán, 2011;Marcelo, Yot and Mayor, 2015).…”
Section: Main Conclusion Of Analyzed Articlesmentioning
confidence: 99%